Opinions of primary school principals in Bunia City (DRC) on the establishment of infirmaries within their schools - NDJABU Justin (Orapuh Journal)
Introduction This study presents the different opinions of the Heads of Primary Schools in the City of Bunia regarding the establishment of an infirmary within their schools.